(untitled) (European journal of volunteering and community-based projects, 2023)
The number of civil service volunteers parallel to Third Sector Entities has increased recently. It is of new interest to assess the impact of the civil service on the outside world and the volunteers involved. The study to investigate these aspects investigates the social impact of universal civil service in the context of reference through constructing the value chain and the causal link between the UDC, the dimension of employability and employment. The employment conditions of volunteers determined through data from the Piedmont Labor Agency and other evidence on the value generated support the analysis of the project spillover on Sustainable Development Goals by determining the change generated and proposing an integrated measurement approach that accommodates different approaches.